Carbon‐Based Electrocatalysts for Efficient Hydrogen Peroxide Production (Adv. Mater. 49/2021). Issue 49 (7th December 2021) - Bu, Yunfei; Wang, Yaobin; Han, Gao‐Feng; Zhao, Yunxia; Ge, Xinlei; Li, Feng; Zhang, Zhihui; Zhong, Qin; Baek, Jong‐Beom
Abstract : Catalysts for H2 O2 Production In article number 2103266, Gao‐Feng Han, Feng Li, Jong‐Beom Baek, and co‐workers review the latest developments of carbon‐based catalysts for the production of hydrogen peroxide (H2 O2 ) from a broad perspective. In particular, designing appropriate functional groups and understanding electrolyte pH effect are important for the further improvement of H2 O2 selectivity via the oxygen reduction reaction.